Preparation and characterization of high-dispersed Pt/C nano-electrocatalysts for fuel cell applications. - Huy, Hoang Anh; Man, Tran Van; Tai, Huynh Thien; Ho, Van Thi Thanh (Vietnam Journal of Science and Technology, 2016)
Synthesis conditions are keys to controlling size and dispersion of Platinum (Pt) nanoparticle structures that is one of the most important goals in improving the electrochemical activity and durability of electrocatalyst as Pt nanoparticles catalyst for fuel cells. In this study, we introduce a simple method to address the effects of the temperature, pH and ethylene glycol enhancers (EG) on the morphology and size distribution of Pt nanoparticles catalyst in electrocatalyst fabrication process Pt nanoparticles on carbon support (Pt NPs/C). By using a facile method, we synthesized Pt NPs/C catalyst with and without using EG at room temperature and 60°C in pH = 6.5 and 11 solutions. The morphology, size, dispersion and activity of Pt nanoparticles catalyst on carbon support were characterized by using X-ray diffraction (XRD), Transmissionelectron microscopy (TEM) and Cyclic Voltammetry (CV). We found that the size, morphology and dispersion of Pt nanoparticles on carbon were strongly affected by adjusting the temperature, pH and the presence of ethylene glycol that could enhance catalytic activity of Platinum for fuel cell applications.